Targeting the Subthalamic Nucleus for Deep Brain Stimulation in Parkinson Disease: The Impact of High Field Strength MRI - Winkler, Dirk; Tittgemeyer, Marc; Strecker, Karl; Goldammer, Axel; Helm, Jochen; Schwarz, Johannes; Meixensberger, Jürgen (IntechOpen, 2012)
None